Respirator use and its impact on particulate matter exposure in aluminum manufacturing facilities - Liu, Sa; Noth, Elizabeth; Eisen, Ellen; Cullen, Mark R.; Hammond, Katharine (Scandinavian Journal of Work, Environment & Health, 2018)
' ' OBJECTIVES ': 'As part of a large epidemiologic study of particulate health effect, this study aimed to report respirator use among total particulate matter (TPM) samples collected in a major aluminum manufacturing company from 1966‒2013 and evaluate the impact of respirator-use adjustment on exposure estimation. ' ' METHODS ': 'Descriptive analyses were performed to evaluate respirator use across facilities and by facility type and job. Protection factors were applied to TPM measurements for recorded respirator use. Estimated TPM exposure for each job ‒ before and after respirator-use adjustment ‒ were compared to assess the impact of adjustment on exposure estimation. ' ' RESULTS ': 'Respirator use was noted for 37% of 12 402 full-shift personal TPM samples. Measured TPM concentration ranged from less than detectable to 8220 mg/m3, with arithmetic mean, median and standard deviation being 10.6, 0.87 and 130 mg/m3, respectively. Respirators were used more often in smelting facilities (52% of TPM measurements) than in fabricating (17%) or refinery facilities (28%) (P<0.01). Sixty-two percent of jobs in smelting facilities were subject to respirator-use adjustment, whereas it was 20% and 70% in fabricating and refinery facilities, respectively. Applying protection factors to TPM measurements significantly reduced estimated job mean TPM exposures and changed exposure categories in these facilities, with larger impact in smelting than fabricating facilities. ' ' CONCLUSIONS ': 'Respirator use varied by time, facility and job. Adjusting respirator use resulted in differential impact in smelting and fabricating facilities, which will need to be incorporated into ongoing epidemiologic studies accordingly.
Keywords: aluminum; aluminum manufacturing facility; assigned protection factor; exposure; fabrication; job exposure matrix; particulate matter; particulate matter exposure; refinery; respirator use; smelter; workplace protection factor